Nanofiber mats functionalized with Mentha piperita essential oil stabilized in a chitosan-based emulsion designed via an electrospinning technique - Lamarra, Javier Andres (2023)
A nanostructured device based on poly(vinyl alcohol) (PVA) loaded with a cross-linked chitosan (CH) emulsion, soy lecithin, and peppermint essential oil (Mentha piperita) was designed for topical applications using an electrospinning instrument coupled to a rotary drum collector. Different suspensions were obtained by varying the PVA to emulsion ratio (PVA:Em) 87.5:12.5, 82:18, and 75:25, using a PVA solution as a control. ATR-FTIR spectra confirmed the interactions among the components of the system. Scanning electron microscopy (SEM) of the mats evinced that the aligned fiber diameter decreased with higher proportions of emulsion while dynamic mechanical analysis (DMA) revealed a decrease in the storage modulus. The entrapment of the functionalized emulsions not only improved the elongation of the matrices but also provided them with greater structural integrity compared to the single PVA matrix. The most favorable formulation in terms of mechanical properties was found to be the 82:18 ratio. After 1 h of close contact between the 82:18 matrix and a porcine skin explant, the latter was examined by confocal microscopy, which revealed the localization of the essential oil mainly on the surface of the stratum corneum (SC).However, after 7 h of contact, the distribution of the peppermint EO throughout the viable epidermis was observed, which was further supported by ATR-FTIR studies. Tailored electrospun matrices would have potential applications as devices for topical or transdermal treatments due to their vehiculization role that allows the diffusion of peppermint essential oil as a skin penetration enhancer.